(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The target of the work is to become counscious and to analizē the most important possible risk for humans safety, when we use forest resources. The branch of forestry is very significant in the Latvia economy. From analising the data of statistics, observations and results of the investigation it is realized, that the for esty branch has one o f the largest numbers (24,4%) of accidents, and doesn't included accidents in farmers forest, small enterprises and individual workers. Causes o f the accidents are incomplete listing of the rules o f forest work and laws, ignorance or taking no notice o f the rules, economical problems, when counsciouly by ignoring the laws. Risk of accidents also occur, when we transport timber, in hunting etc.